ANALISIS KEPATUHAN PEMBAYARAN PAJAK BUMI DAN BANGUNAN DI KABUPATEN BOGOR (STUDI BERDASARKAN SURAT PEMBERITAHUAN PAJAK TERHUTANG DESA LIGARMUKTI) - Adela, Sintia; Irawati, Irawati (Institut Ilmu Sosial dan Manajemen STIAMI, 2025)
Land and Building Tax is a tax imposed on individuals who own land, whether managed or unmanaged. Land and Building Tax is a standalone tax, and its revenue belongs to the largest category. This research aims to analyze the compliance with Land and Building Tax payment in Bogor Regency, specifically in Ligarmukti Village. In this study, the researcher aims to determine the extent of tax compliance among residents residing in Ligamukti Village and identify factors preventing the compliance rate in Ligamukti Village from reaching 100%. This is a qualitative research with a descriptive approach. Data collection techniques include observation, interviews, and documentation. The results of this research indicate that there is a significant number of residents who are negligent in paying taxes, and there is a lack of socialization regarding the importance of tax payment.